The Influence of Competence, Training, and Emotional Intelligence on Performance: Mediation of Productivity at Dinas Tenaga Kerja and Transmigrasi off Bantul Regency - Muhammad Fatkhurohman Albashori; Sri Wahyuning; Himawan Agung Nugroho; Muhammad Nasrip (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: Employee performance is a critical determinant of organizational success, influenced by various factors including competence, training, and emotional intelligence. However, the mechanisms through which these factors affect performance, particularly the mediating role of productivity, remain underexplored in the context of Indonesian government institutions. This study examines the influences of competency, training, and emotional intelligence on employee performance with productivity as a mediating variable at Dinas Tenaga Kerja dan Transmigrasi Kabupaten Bantul. Method: This quantitative study employed a causal associative design with a survey approach. Data were collected from 50 respondents selected using purposive sampling. The analysis utilized path analysis with SmartPLS 3 software to examine both direct and indirect effects among the variables. Results: The findings demonstrate that competency, training, and emotional intelligence each have significant positive effects on both employee productivity and performance. Competency showed the strongest direct effect on productivity (β = 0.45), followed by emotional intelligence (β = 0.40) and training (β = 0.37). Productivity significantly influences performance (β = 0.50). Furthermore, productivity partially mediates the relationships between competency, training, and emotional intelligence on performance, with indirect effects of 0.225, 0.185, and 0.200 respectively. Conclusion: Enhancing employee performance requires a comprehensive approach that develops competencies, provides relevant training, and fosters emotional intelligence, all of which work through productivity improvements. Organizations should prioritize competency development programs, quality training initiatives, and emotional intelligence training to maximize employee performance outcomes.